Orthohydrogen and parahydrogen conversion catalyst and preparation method thereof

By using ultrasonic and mechanical dispersion technology to prepare hydrated iron oxide catalysts at room temperature, the problems of low specific surface area and insufficient particle strength of the existing catalyst are solved, and the preparation of high-efficiency and low-energy consumption of positive secondary hydrogen conversion catalysts are achieved.

CN119386868AActive Publication Date: 2025-02-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310922783.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-07
Estimated Expiration
2043-07-26

AI Technical Summary

Technical Problem

The existing secondary hydrogen conversion catalysts have low specific surface area and insufficient particle strength, resulting in low catalytic activity, low synthesis efficiency and high energy consumption.

Method used

Using the combined action of ultrasonic dispersion and mechanical dispersion, the iron salt solution and inorganic alkali solution are mixed at room temperature to form a colloidal mixture. After standing, washing, drying and crushing, hydration with large specific surface area and high physical strength is obtained. Iron oxide catalyst.

Benefits of technology

The specific surface area and physical strength of the catalyst are improved, the reaction temperature and energy consumption are reduced, and the preparation efficiency and catalytic activity are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386868A_ABST
    Figure CN119386868A_ABST
Patent Text Reader

Abstract

The invention discloses an ortho-parahydrogen conversion catalyst and a preparation method thereof, the catalyst comprises an active component hydrated iron oxide, the hydrated iron oxide is in a weak crystal state, and the microscopic particle size is 3-10nm; the ortho-parahydrogen conversion catalyst is granular, the particle size is 20-80 meshes, the particle crushing strength is 5-13N / particle, and the specific surface area is 160-300m < 2 > / g. The preparation method comprises the following steps: (1) under the simultaneous action of ultrasonic dispersion and physical dispersion, mixing a ferric salt solution with inorganic alkali liquor to form a colloidal mixture, and then standing the colloidal mixture for 0.5-5 hours; and (2) washing and separating the mixture in the step (1), and then drying, crushing and screening to obtain the ortho-parahydrogen conversion catalyst. The ortho-parahydrogen conversion catalyst is large in specific surface area, high in physical strength, simple in preparation method, low in reaction temperature, low in energy consumption, high in preparation efficiency and high in ortho-parahydrogen conversion catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic conversion of normal para-hydrogen, and in particular relates to a catalyst for normal para-hydrogen conversion and a preparation method thereof. Background Art

[0002] Liquid hydrogen is a highly efficient liquid fuel with broad application prospects in chemical production, aerospace engineering, hydrogen-powered vehicles, etc. Liquid hydrogen has the advantages of being easy to store and measure, and has become one of the important ways to use, store and transport hydrogen energy.

[0003] A hydrogen molecule is composed of two hydrogen atoms with different nuclear spin directions, of which orthohydrogen is symmetrical and parahydrogen is antisymmetric. Both orthohydrogen and parahydrogen can exist stably in liquid and gaseous states, and their equilibrium concentrations are affected by temperature. At room temperature, the orthohydrogen content in hydrogen is 25% and the parahydrogen content is 75%, which is called normal hydrogen or standard hydrogen. When the temperature drops, orthohydrogen will spontaneously convert to parahydrogen. At the standard boiling point of liquid hydrogen, the parahydrogen content can reach 99.8%. In the absence of an external catalyst, the spontaneous conversion of the orthohydrogen to the parahydrogen state is very slow, and the heat released during the conversion process is greater than the vaporization heat of liquid hydrogen, which will cause vaporization loss of liquid hydrogen. In order to quickly complete the conversion of orthohydrogen to parahydrogen while liquefying hydrogen, the development of high-performance orthohydrogen conversion catalysts is crucial for the production of liquid hydrogen.

[0004] Currently, amorphous hydrated iron oxide is mainly used as a catalyst for the conversion of ortho-parahydrogen.

[0005] CN202210029537.5 provides a method for preparing nano hydrated iron oxide. A hydrothermal method is used to obtain nano hydrated iron oxide with high crystallinity and a particle size of 15 to 25 nm. The product has a large particle size and a low specific surface area.

[0006] CN202111354244.6 discloses a method for preparing a doped parahydrogen conversion catalyst. An iron salt solution and a metal ion solution to be doped are prepared separately, and the metal ion solution to be doped is dripped into the iron salt solution in a certain proportion, and then an appropriate amount of alkali solution is added. The precipitate obtained by hydrothermal reaction of the mixed solution is washed, dried, and ground to obtain a hydrated iron oxide parahydrogen catalytic conversion catalyst. The doped iron oxide prepared by the high-temperature hydrothermal method has a large grain size (300-1000nm), a high crystallinity of the product, and a small specific surface area. At the same time, the high-temperature reaction time used is too long, the synthesis efficiency is low, and the energy consumption is high.

[0007] CN202210832769.4 provides a catalyst for the conversion of ortho-parahydrogen and a preparation method thereof. The catalyst is a fiber magnetic catalyst FeMnO doped with Fe atoms. x, having a fibrous structure with a diameter of 2 to 5 nm and a length of 100 nm to 500 nm, a large product particle size and a low specific surface area. This method requires the use of a hydrothermal reaction, which consumes a lot of energy, and because a manganese oxide precursor needs to be prepared, the preparation cost is also high.

[0008] CN201910782910.2 discloses a method for preparing hydrated iron oxide, adding a weakly basic compound to a ferric chloride composite solution, aging, filtering, and dispersing the filter cake in an ammonium bicarbonate solution, filtering, and drying to obtain hydrated iron oxide. The method uses a weak base as a precipitant, and the crystalline phase of the product obtained by the reaction at room temperature and pressure is mainly amorphous. On the other hand, the method acts on the filter cake with ammonium bicarbonate, and then uses the pore-forming effect of ammonium bicarbonate pyrolysis to increase the specific surface area of ​​the product, but it will cause a significant decrease in the strength of the dried particles. At the same time, the impurities additionally introduced by the ammonium bicarbonate impurities used are difficult to control, which is not conducive to the control of the index of the catalyst for the catalytic conversion of parahydrogen.

[0009] [Progress in Fine Petrochemicals, 2010, 11 (7): 26-31] investigated the effect of the order of adding iron salt and alkali on the properties of iron hydroxide products. It was found that the specific surface area of ​​the product obtained by adding iron salt solution to alkali solution and alkali solution to iron salt solution was larger than that of the latter, but in general, the specific surface area of ​​both products was small (less than 150m 2 / g), the obtained products are all amorphous crystals.

[0010] Specific surface area and particle strength are important control indicators of catalytic materials. The hydrated iron oxide used in the above-mentioned para-hydrogen conversion catalysis has a low specific surface area or weak particle strength, which is not conducive to improving the performance of the para-hydrogen catalyst. Summary of the invention

[0011] In view of the deficiencies of the prior art, the present invention provides a para-hydrogen conversion catalyst and a preparation method thereof. The para-hydrogen conversion catalyst of the present invention has a large specific surface area, high physical strength, a simple preparation method, a low reaction temperature, low energy consumption, high preparation efficiency, and high catalytic activity for para-hydrogen conversion.

[0012] The para-hydrogen conversion catalyst of the present invention comprises an active component, hydrated iron oxide, which is in a weakly crystalline state and has a microscopic particle size of 3 to 10 nm; the para-hydrogen conversion catalyst is in a granular form, with a particle size of 20 to 80 meshes, a particle crushing strength of 5 to 13 N / particle, and a specific surface area of ​​160 to 300 m 2 / g.

[0013] In the ortho-parahydrogen conversion catalyst of the present invention, the weakly crystalline state has the following characteristics: (1) in the XRD spectrum, the peak intensity of all characteristic diffraction peaks is compared with the baseline intensity at the position (2θ), and there is no diffraction peak whose ratio is greater than 2 and whose half-height width of the diffraction angle 2θ is less than 2°; (2) there are discernible lattice fringe images in the high-magnification (200,000 times and above) transmission electron microscope images or discernible diffraction spots or diffraction rings in the electron diffraction spectrum.

[0014] The preparation method of the ortho-parahydrogen conversion catalyst of the present invention comprises the following contents: (1) Mixing the iron salt solution and the inorganic alkali solution under the simultaneous action of ultrasonic dispersion and mechanical dispersion to form a colloidal mixture, and then leaving the colloidal mixture to stand for 0.5-5 hours; (2) washing and separating the mixture of step (1), and then drying the mixture, wherein the drying process comprises: a first stage, a drying temperature of 40 to 100° C., and a drying time of 6 to 96 hours; a second stage, a drying temperature of 100 to 200° C., and a drying time of 1 to 48 hours, and the drying atmosphere is air atmosphere; (3) The dried material is crushed and sieved to obtain a catalyst for the conversion of normal and para hydrogen.

[0015] In the method of the present invention, step (1) is generally carried out at room temperature, wherein the room temperature is 10 to 45°C.

[0016] In the method of the present invention, the iron salt in step (1) is ferric chloride and / or ferric sulfate; the iron salt solution in step (1) is Fe 3+ The calculated concentration is 0.10 to 1.5 mol / L, preferably 0.15 to 1.0 mol / L.

[0017] In the method of the present invention, the inorganic base in step (1) is one or more of sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, sodium carbonate, sodium bicarbonate or ammonium bicarbonate, preferably one or more of sodium hydroxide, potassium hydroxide, rubidium hydroxide or cesium hydroxide; the concentration of the inorganic alkali solution is OH - The calculated concentration is 0.5 to 2.0 mol / L, preferably 1.0 to 1.5 mol / L.

[0018] In the method of the present invention, the iron salt solution in step (1) is Fe 3+ Calculate with inorganic alkali solution to OH - Gage, OH - / Fe 3+ The molar ratio is 3.0 to 4.5.

[0019] In the method of the present invention, the ultrasonic dispersion conditions in step (1) are: ultrasonic frequency 20-100 kHz, ultrasonic power density acting on the reaction material is 10-1000 W / L, and ultrasonic temperature is 10-45°C; the preferred conditions for ultrasonic dispersion are: ultrasonic frequency 40-80 KHz, ultrasonic power density 20-100 W / L, and ultrasonic temperature maintained at 20-35°C.

[0020] In the method of the present invention, the mechanical dispersion in step (1) includes but is not limited to any method and operating conditions that are conducive to rapid and uniform mixing of the materials, such as mechanical stirring, magnetic stirring, shaking table, shear stirring, etc.

[0021] In the method of the present invention, the order and method of adding the materials in step (1) are not particularly limited, but preferably the alkali solution is added to the iron salt solution, which can be added all at once or in batches, preferably in batches.

[0022] In the method of the present invention, the separation in step (2) can be carried out by natural sedimentation, centrifugation, vacuum filtration or filter press to separate the washed suspension into solid and liquid to obtain a solid phase.

[0023] In the method of the present invention, the degree of washing and filtering in step (2) must satisfy the requirement that the mass content of sodium in the catalyst composition obtained finally, calculated as Na2O, is less than 0.1%, preferably less than 0.01%. Deionized water is generally used for the washing operation.

[0024] In the method of the present invention, the drying treatment in step (2) is further preferably as follows: in the first stage, the drying temperature is 60-80°C and the drying time is 12-24 hours; in the second stage, the drying temperature is 120-160°C and the drying time is 6-24 hours.

[0025] In the method of the present invention, the crushing in step (3) refers to converting the large-sized dry filter cake into small-sized particles by any means such as knocking, rolling, etc.

[0026] The screening in step (3) refers to screening out the small particles formed by crushing through a standard sieve, screening 20-80 mesh particles, more preferably 30-60 mesh particles as the final molded particles, thereby forming the high-strength, high specific surface area normal-parahydrogen conversion catalyst of the present invention.

[0027] The invention discloses an application of the ortho-parahydrogen conversion catalyst in ortho-parahydrogen conversion reaction.

[0028] When preparing hydrated iron oxide, the present invention always uses ultrasonic dispersion and physical dispersion to work together during the reaction process, and synergistically strengthens dispersion from the macroscopic and microscopic perspectives, which can avoid colloids or precipitation aggregation to form larger particles, thereby maintaining a highly dispersed state, which is beneficial to obtaining smaller reactant particles and improving the specific surface area of ​​the product. The present invention can generate weakly crystalline hydrated iron oxide at room temperature through micro-area shearing and cavitation formed by ultrasound, and studies have found that it is beneficial to improve the activity of the catalyst. Through the two-stage drying method, it can prevent the hydrated iron oxide in the filter cake from undergoing a secondary hydrothermal reaction caused by direct high-temperature drying, and can also improve the strength of the small particles obtained by crushing the dried filter cake. The present invention does not use a high-temperature hydrothermal synthesis method, and has a low reaction temperature, low energy consumption, high efficiency, a large specific surface area of ​​the obtained hydrated iron oxide, and high strength of the formed particles, and excellent activity for catalytic conversion of ortho-parahydrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a transmission electron microscope image of the hydrated iron oxide prepared in Example 1.

[0030] Figure 2 This is the X-ray diffraction spectrum of the hydrated iron oxide prepared in Example 1.

[0031] Figure 3 This is the electron diffraction spectrum of the hydrated iron oxide prepared in Example 1.

[0032] Figure 4 This is the X-ray diffraction spectrum of the iron oxide prepared in Comparative Example 1. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with the examples. The Na2O content in the catalyst is tested by XRF method; the specific surface area is tested by low temperature nitrogen adsorption method, and the specific surface area value is calculated according to the BET method; the crushing strength of the formed particles is measured by a strength meter, and it is stipulated that particles of 35 to 40 mesh are screened, and 50 particles are randomly selected to test their average strength as the crushing strength of the catalyst; the nanoparticle size and lattice image of hydrated iron oxide are observed by transmission electron microscopy; the method for determining the degree of crystallinity of the sample is defined as follows: (1) For strongly crystalline samples, in its XRD spectrum, the peak intensity of all characteristic diffraction peaks is compared with the baseline intensity at the position (2θ), and there is at least one diffraction peak with a ratio greater than 2, and the half-height width of the diffraction angle 2θ is less than 2º; (2) For weakly crystalline samples, there is no diffraction peak in its XRD spectrum that meets the above-mentioned strong crystallization judgment conditions, but there should be a discernible lattice fringe image in the high-magnification transmission electron microscope image, or there should be discernible diffraction spots or diffraction rings in the electron diffraction spectrum. The ortho-parahydrogen content is calculated by gas chromatography, and the parahydrogen conversion rate is calculated as follows: conversion rate = (parahydrogen content% - 25%) / 25.8%, wherein the ortho-hydrogen and para-hydrogen contents of the raw hydrogen are calculated as 75% and 25% respectively, and at liquid nitrogen temperature (77K), the parahydrogen equilibrium concentration is calculated as 50.8%. Example 1

[0034] Prepare 1.0 mol / L sodium hydroxide solution and 0.5 mol / L ferric chloride solution respectively. At room temperature (25°C), under the conditions of mechanical stirring and ultrasonic dispersion (40kHz, 20W / L), add a certain amount of sodium hydroxide solution to the ferric chloride solution to meet the OH - / Fe 3+ The molar ratio is 3.5, and a suspension is formed. After standing for 2 hours, the suspension is repeatedly washed with water and filtered to remove the sodium ions in the sample to meet the index requirements. The washed product is dried at 60° C. for 12 hours and then at 140° C. for 12 hours to obtain the hydrated iron oxide, which is crushed and screened to obtain particles of appropriate size as a catalyst for ortho-parahydrogen conversion.

[0035] After testing, there is no obvious diffraction peak in the X-ray diffraction spectrum, indicating that the crystallinity is not high, but obvious lattice fringes can be observed in the transmission electron microscope image with a magnification of 200,000 times, and some diffraction spots are also shown in the selected area electron diffraction spectrum, indicating that the obtained hydrated iron oxide is weakly crystalline. The average particle size of hydrated iron oxide is 5.9nm. The specific surface area of ​​the catalyst is 257m 2 / g, and the average strength is 6.7N / particle. The normal and para hydrogen conversion performance test is shown in Table 1. Example 2

[0036] Prepare 1.5 mol / L sodium hydroxide solution and 1.0 mol / L ferric chloride solution respectively. At room temperature (30°C), under the conditions of mechanical stirring (300 rpm) and ultrasonic dispersion (100 KHz, 100 W / L), add a certain amount of ferric chloride solution to the sodium hydroxide solution to meet the OH content in the system. - / Fe 3+ The molar ratio is 3.5, and a suspension is formed. After standing for 4 hours, the suspension is repeatedly washed and filtered with water to remove the sodium ions in the sample to meet the index requirements. The washed material is dried at 60° C. for 12 hours and then at 160° C. for 12 hours to obtain the hydrated iron oxide, which is crushed and screened to obtain particles of appropriate size as a catalyst for ortho-parahydrogen conversion.

[0037] The test showed that the obtained hydrated iron oxide was in a weak crystalline state, with an average particle size of 7.3nm and a specific surface area of ​​239m 2 / g. The average strength of the catalyst particles is 7.2N / particle. The normal and para hydrogen conversion performance tests are shown in Table 1. Example 3

[0038] Prepare 1.5 mol / L sodium carbonate solution and 1.0 mol / L ferric chloride solution respectively. At 45°C, under the conditions of mechanical stirring (300 rpm) and ultrasonic dispersion (40 kHz, 100 W / L), add a certain amount of sodium hydroxide solution to the ferric chloride solution to meet the OH - / Fe 3+ The molar ratio is 3.5, and a suspension is formed. After standing for 0.5 hours, the suspension is repeatedly washed and filtered with water to remove the sodium ions in the sample to meet the index requirements. The washed material is dried at 80° C. for 10 hours and then at 105° C. for 12 hours to obtain the hydrated iron oxide, which is crushed and screened to obtain particles of appropriate size as a catalyst for ortho-parahydrogen conversion.

[0039] The test showed that the obtained hydrated iron oxide was weakly crystalline, and the average particle size of the hydrated iron oxide was 5.4nm. The specific surface area of ​​the catalyst was 297m 2 / g, and the average particle strength is 5.8N / particle. The normal and para hydrogen conversion performance test is shown in Table 1. Example 4

[0040] The sample was prepared according to the ratio of Example 3 in CN201910782910.2, and other conditions were the same as Example 3.

[0041] The test showed that the obtained hydrated iron oxide was weakly crystalline, with an average particle size of 6.1 nm. The average strength of the catalyst particles was 8.2 N / particle. The specific surface area was 286 m 2 / g. After being crushed into particles of appropriate size, a catalyst for normal-parahydrogen conversion is formed. The normal-parahydrogen conversion performance test is shown in Table 1. Comparative Example 1

[0042] The preparation conditions were the same as in Example 1, except that only physical stirring was used without applying ultrasonic dispersion.

[0043] The test showed that the obtained iron oxide was amorphous crystalline, with an average particle size of 15.7 nm and a specific surface area of ​​113 m 2 / g. The normal and para hydrogen conversion performance test is shown in Table 1. Comparative Example 2

[0044] Iron oxide was prepared according to the method provided in Example 1 of CN202210029537.5. The iron oxide grain size was 24 nm and the crystallinity was high. After testing, its specific surface area was only 64 m 2 / g. The normal and para hydrogen conversion performance test is shown in Table 1. Comparative Example 3

[0045] According to the method provided in Example 1 of CN202111354244.6, iron oxide was prepared. The obtained doped iron oxide had a grain size of 300-1000 nm, and the iron oxide showed strong crystallinity. The tested specific surface area was only 48 m 2 / g. The normal and para hydrogen conversion performance test is shown in Table 1. Comparative Example 4

[0046] Hydrated iron oxide was prepared according to the method of Example 3 of CN201910782910.2. After testing, the obtained hydrated iron oxide was amorphous crystalline, with an average particle size of 5.8 nm and a specific surface area of ​​251 m 2 / g, and the average particle strength is only 2.4N / particle. The normal and para hydrogen conversion performance test is shown in Table 1.

[0047] Comparative Example 5 The sample was prepared according to the method of Example 1. The difference is that the drying stage is not segmented, but directly dried at 140°C for 12 hours. After testing, a strong peak appeared in the XRD spectrum of the obtained hydrated iron oxide, indicating that the obtained hydrated iron oxide has a high degree of crystallinity. The ortho-parahydrogen conversion performance test is shown in Table 1.

[0048] Table 1 Parahydrogen conversion rate of catalysts Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Parahydrogen conversion rate % 97.5 97.8 98.6 98.9 95.9 90.4 89.7 96.8 94.2 Test conditions: catalyst particle size 30-40 mesh, activation conditions 130℃ vacuum drying for 12 hours, evaluation temperature 77K, volume space velocity 400min -1

Claims

1. A parahydrogen conversion catalyst, characterized in that: The invention comprises an active component of hydrated iron oxide, which is in a weakly crystalline state; the weakly crystalline state has the following characteristics: (1) in the XRD spectrum, the peak intensity of all characteristic diffraction peaks is compared with the baseline intensity at the position (2θ), and there is no diffraction peak whose ratio is greater than 2 and whose half-height width of the diffraction angle 2θ is less than 2°; (2) there are discernible lattice fringe images in the high-magnification (more than 200,000 times) transmission electron microscope image or discernible diffraction spots or diffraction rings in the electron diffraction spectrum.

2. The catalyst according to claim 1, characterized in that: The microscopic particle size of hydrated iron oxide is 3 to 10 nm.

3. The catalyst according to claim 1, characterized in that: The catalyst for the conversion of normal and secondary hydrogen is in granular form, with a particle size of 20-80 mesh, a particle crushing strength of 5-13N / particle, and a specific surface area of ​​160-300m 2 / g.

4. A method for preparing a parahydrogen conversion catalyst according to any one of claims 1 to 3, characterized in that The method comprises the following contents: (1) mixing an iron salt solution and an inorganic alkali solution under the simultaneous action of ultrasonic dispersion and mechanical dispersion to form a colloidal mixture, and then standing the mixture for a period of time; (2) washing and separating the mixture obtained in step (1), and then drying the mixture, wherein the drying process comprises: a first stage, a drying temperature and time of 40 to 100° C., and a drying time of 6 to 96 hours; a second stage, a drying temperature and time of 100 to 200° C., and a drying time of 1 to 48 hours, and the drying atmosphere is an air atmosphere; and (3) crushing and screening the dried material to obtain a catalyst for ortho-parahydrogen conversion.

5. The method according to claim 4, characterized in that: The iron salt in step (1) is ferric chloride and / or ferric sulfate; the iron salt solution in step (1) is Fe 3+ The calculated concentration is 0.10 to 1.5 mol / L, preferably 0.15 to 1.0 mol / L.

6. The method according to claim 4, characterized in that: The inorganic base in step (1) is one or more of sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, sodium carbonate, sodium bicarbonate or ammonium bicarbonate, preferably one or more of sodium hydroxide, potassium hydroxide, rubidium hydroxide or cesium hydroxide; the concentration of the inorganic alkali solution is OH - The calculated concentration is 0.5 to 2.0 mol / L, preferably 1.0 to 1.5 mol / L.

7. The method according to claim 4, characterized in that: The iron salt solution in step (1) is Fe 3+ Calculate with inorganic alkali solution to OH - Gage, OH - / Fe 3+ The molar ratio is 3.0 to 4.

5.

8. The method according to claim 4, characterized in that: The ultrasonic dispersion conditions in step (1) are: ultrasonic frequency 20-100 kHz, ultrasonic power density acting on the reaction material is 10-1000 W / L, and ultrasonic temperature is 10-45°C; the preferred conditions for ultrasonic dispersion are: ultrasonic frequency 40-80 KHz, ultrasonic power density 20-100 W / L, and ultrasonic temperature maintained at 20-35°C.

9. The method according to claim 4, characterized in that: The mechanical dispersion in step (1) is one or more of mechanical stirring, magnetic stirring, shaking table or shear stirring.

10. The method according to claim 4, characterized in that: The colloidal mixture in step (1) is allowed to stand for 0.5-5 hours.

11. The method according to claim 4, characterized in that: The drying treatment in step (2) is further preferably as follows: in the first stage, the drying temperature is 60-80°C and the drying time is 12-24 hours; in the second stage, the drying temperature is 120-160°C and the drying time is 6-24 hours.

12. The method according to claim 4, characterized in that: The screening in step (3) refers to screening out the small particles formed by crushing through a standard sieve, and screening particles of 20 to 80 mesh.

13. Use of the para-hydrogen conversion catalyst according to any one of claims 1 to 4 in a para-hydrogen conversion reaction.

Citation Information

Patent Citations

  • Preparation method of hydrated iron oxide

    CN110422886A

  • Para-hydrogen enrichment device and method for nuclear magnetic resonance para-hydrogen induced polarization

    CN110568000A

  • Nano hydrated iron oxide as well as preparation method and application thereof

    CN114314677A

  • Catalyst for catalyzing ortho-parahydrogen conversion as well as preparation method and application of catalyst

    CN114367288A

  • Orthohydrogen-parahydrogen conversion catalyst and orthohydrogen-parahydrogen conversion method

    WO2022249886A1